2023
DOI: 10.3389/fmolb.2023.1184767
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the ultrasonic treatment of working fluids on electrospun amorphous solid dispersions

Abstract: Based on a working fluid consisting of a poorly water-soluble drug and a pharmaceutical polymer in an organic solvent, electrospinning has been widely exploited to create a variety of amorphous solid dispersions However, there have been very few reports about how to prepare the working fluid in a reasonable manner. In this study, an investigation was conducted to determine the influences of ultrasonic fluid pretreatment on the quality of resultant ASDs fabricated from the working fluids. SEM results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…One reason for the popularity of electrospinning is the facile building of an apparatus that is very useful and convenient for creating nanofibers and polymeric nanocomposites. 41,67,68 Similar to electrospinning, an electrospraying system is easy to set up. The key is to bring the working fluid and the electrostatic energy together to produce a solid product.…”
Section: Resultsmentioning
confidence: 99%
“…One reason for the popularity of electrospinning is the facile building of an apparatus that is very useful and convenient for creating nanofibers and polymeric nanocomposites. 41,67,68 Similar to electrospinning, an electrospraying system is easy to set up. The key is to bring the working fluid and the electrostatic energy together to produce a solid product.…”
Section: Resultsmentioning
confidence: 99%
“…This breakthrough enabled the creation of novel drug-loaded sheath nanofibers, which exhibited delayed quick release, prolonged slow-release, reduced tail break release, and the complete release of drug molecules. Non-spinnable liquids encompass pure solvents, surfactants, or salt solutions, significantly broadening the application scope of electrospun nanofibers [ 46 , 47 ].…”
Section: Preparation Of Drug-loaded Nanofibers Via Electrospinningmentioning
confidence: 99%
“…These phenomena suggested that the drug BH was converted into amorphous composites in all of them after the electrospraying or electrospinning processes. An amorphous state of the drug is favorable for its dissolution and the manipulation of a certain controlled release profile from the matrices [75,76]. FTIR spectra of the raw materials (CA, PVP, and BH) and their EHDA p shown in the left part of Figure 7.…”
Section: The Physical State and Compatibilitymentioning
confidence: 99%